Microsatellite primers identified by 454 sequencing in the floodplain tree species Eucalyptus victrix (Myrtaceae). - Nevill, Paul; Bradbury, D.; Jørgensen, T.; Krauss, S.; Samaraweera, S.; Gardner, M. (2013)
UNLABELLED: • PREMISE OF THE STUDY: Microsatellite primers were developed for Eucalyptus victrix (Myrtaceae) to evaluate the population and spatial genetic structure of this widespread northwestern Australian riparian tree species, which may be impacted by hydrological changes associated with mining activity. • METHODS AND RESULTS: 454 GS-FLX shotgun sequencing was used to obtain 1895 sequences containing putative microsatellite motifs. Ten polymorphic microsatellite loci were identified and screened for variation in individuals from two populations in the Pilbara region. Observed heterozygosities ranged from 0.44 to 0.91 (mean: 0.66) and the number of alleles per locus ranged from five to 25 (average: 11). • CONCLUSIONS: These microsatellite loci will be useful in future studies of population and spatial genetic structure in E. victrix, and inform the development of seed sourcing strategies for the species.